EDUKASI PENGELOLAAN SAMPAH ORGANIK MELALUI PEMASANGAN PLANG INFORMASI DAN PENGENALAN TEBE MODERN - Maria Frangela Suriti Sangu; Pande Made Dwi Pranita; Alfonsus Saingo; Ni Luh Gishcea Puspita Dewi; Anak Agung Adimas Jaya Pramana; Kevin Michael Marvel Styawan; Mardinon Ervinto Tanggela; Reinardis Halom; Ni Kadek Rini Purwati; Ni Luh Putu Cahayani (PUAN INDONESIA, 2026)
Organic waste management remains a critical environmental challenge in rural communities, driven by low public awareness and inadequate waste handling practices. This paper reports on a community service activity conducted through the Community Service Program (KKN) at Banjar Mukti, Desa Singapadu, Bali, involving students from Universitas PGRI Mahadewa Indonesia. The activity aimed to educate the community about organic waste management through two main interventions: (1) installation of informational signboards (plang sampah) at the final waste disposal site (TPA), displaying the decomposition timeline of various waste types; and (2) introduction of modern organic waste bins (tebe modern) as an alternative to open burning. Observations prior to the activity revealed that the majority of households still disposed of organic waste by burning or dumping indiscriminately, with no separation between organic and inorganic waste. The informational signboards presented data on waste decomposition times, ranging from weeks for organic matter to hundreds of years for plastic and glass, to raise community awareness. Due to program time constraints, post-activity behavioral change could not be formally measured. However, community members showed positive responses during the activity. Continued mentoring and follow-up evaluation are recommended to assess long-term impact.